Corporate sustainability accounting disclosure : the impact of financial performance, governance attributes and ownership structure - Al Amosh, Hamzeh
Sustainability accounting disclosure among corporations continue to receive global attention from various takeholders including communities, governments and investors. This is due to the growing demand for information and sensitivity of society to understand how companies plan and manage sustainability issues in their operations. Thus, companies are now attempting to balance their financial goals with non-financial performance, particularly sustainability. The trend is now growing in developing countries where r sources are limited such as in Jordan. This thesis examines the effect of three determining factors which are financial performance, governance attributes and ownership structure on the level of sustainability accounting disclosures in three dimensions among industry players in Jordan. The three dimensions are: (i) economic; (ii) social; and (iii) environmental. The study used secondary data collected from annual reports of companies listed on Jordan Stock Exchange for the period 2012-2017. A panel data of 306 company-years was obtained, and content analysis technique was applied. STATA software was used to analyse the data and the Ordinary Least Squares (OLS) regression were performed. Th re is an upward trend in the disclosure level of sustainability accounting during this period of study. Regarding the determinants, board size, foreign ownership, company size and type of industry show positive effects on the disclosure of all of the u tainability accounting dimensions. On the other hand, company profitability positively affects the environmental disclosure only. The findings indicate that the board activity positively affects all of the dimensions of sustainability disclosure while managerial ownership contributes significantly to economic disclosure only. In contrast, non-executive directors show a negative impact on the sustainability disclosure and block shareholding contributes negatively to economic disclosure. Moreover, the results did not provide support for the significant effect of other independent variables on the level of accounting disclosure. The study provides empirical evidence on how listed companies in Jordan are practicing sustainability accounting disclosures. The research outcomes also provide directions for government agencies and decision makers to enhance sustainability disclosure and suggest future research on disclosure and corporate reporting. The current study also contributes to the literature by introducing a recent topic in the accounting disclosures, namely issues of sustainability accounting in emerging countries like Jordan. In addition, the current study discusses theoretical implications to the stakeholder theory and the legitimacy theory which form the bases for this research framework and their relationships to the interpretation of sustainability disclosure practices.